Peran Strategis Media Massa Dalam Edukasi Masyarakat Terhadap Bahaya Korupsi - Ramadhani, Mahfud (Belom Bahadat, 2025)
This research aims to examine the role of mass media in increasing public awareness of the dangers of corruption. Corruption is one of the big problems that hinders the development and welfare of society, so public understanding of the negative impacts of corruption is very important. Mass media, as a broad and easily accessible information channel, has great potential in spreading anti-corruption messages. Through a qualitative approach, this research analyzes how mass media, both print, electronic and digital, convey information and build public awareness about the dangers of corruption. The research results show that the mass media plays an important role in shaping public opinion, educating the public, and motivating them to get involved in preventing and eradicating corruption. However, challenges in maximizing the role of mass media also need to be taken into account, such as the diversity of information sources and political interests which can affect the objectivity of reporting. Therefore, it is important for the mass media to continue to strengthen its commitment to disseminating accurate information and educating the public to be more critical of corrupt practices.